CO2 sequestration in microbial electrolytic cell-anaerobic digestion system combined with mineral carbonation for sludge hydrolysate treatment - He, Wanying (Waste management (New York, N.Y.), 2024)
Copyright © 2024 Elsevier Ltd. All rights reserved.